IoT-Based Banknotes Saving Automation System - Prasasti, Anggunmeka Luhur; Septiawan, Reza Rendian; Alfarisi, Muhammad Haekal (Universitas Telkom, 2023)
Many problems occur with traditional savings, such as users not knowing the nominal amount that has been saved later, and the authenticity of the money saved. To overcome this problem, the